Maritime Cooperation Between Indonesia And China In South China Sea - Ainun Djaria; Seniwati Seniwati (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
The maritime conflict between Indonesia and China in the South China Sea arises from overlapping claims, particularly concerning Indonesia’s Exclusive Economic Zone (EEZ) near the Natuna Islands. China’s assertion of sovereignty through its Nine-Dash Line, which Indonesia does not recognize under the 1982 United Nations Convention on the Law of the Sea (UNCLOS), has fueled tensions. These have been exacerbated by aggressive actions, including Chinese vessels' incursions and illegal fishing within Indonesia’s EEZ. Despite these conflicts, both nations emphasize maritime cooperation to enhance bilateral ties.This study examines the dynamics of Indonesia-China maritime cooperation and conflicts in the South China Sea and their implications for regional stability. Employing a literature-based methodology, it investigates challenges and potential resolutions, including diplomacy and third-party mediation through bodies like the International Court of Justice. The findings highlight that resolving disputes effectively requires a legal framework and multilateral collaboration through ASEAN. The study concludes with recommendations for bolstering diplomatic engagement and sustainably managing maritime resources to ensure stability across the Indo-Pacific region.